A multicentre cross‐sectional observational study of cancer multidisciplinary teams: Analysis of team decision making. (13th August 2020) - Soukup, Tayana; Lamb, Benjamin W.; Morbi, Abigail; Shah, Nisha J.; Bali, Anish; Asher, Viren; Gandamihardja, Tasha; Giordano, Pasquale; Darzi, Ara; SA Green, James; Sevdalis, Nick
Abstract: Background: Multidisciplinary teams (MDT) formulate expert informed treatment recommendations for people with cancer. We set out to examine how the factors proposed by the functional perspective of group decision making (DM), that is, interaction process, internal factors (factors emanating from within the group such as group size), external circumstances (factors coming from the outside of the team), and case‐complexity affect the quality of MDT decision making. Methods: This was a cross‐sectional observational study. Three cancer MDTs were recruited with 44 members overall and 30 of their weekly meetings filmed. Validated observational instruments were used to measure quality of DM, interactions, and complexity of 822 case discussions. Results: The full regression model with the variables proposed by the functional perspective was significant, R 2 = 0.52, F (20, 801) = 43.47, P < .001, adjusted R 2 = 0.51. Positive predictors of DM quality were asking questions ( P = .001), providing answers ( P = .001), team size ( P = .007), gender balance ( P = .003), and clinical complexity ( P = .001), while negative socioemotional reactions ( P = .007), gender imbalance ( P = .003), logistical issues ( P = .001), time‐workload pressures ( P = .002), and time spent in the meeting ( P = .001) were negative predictors. Second half of the meetings also saw significant decrease in the DM quality ( P = .001), interactions ( P = .001), group size ( P = .003), and clinical complexity ( P = .001), and an increase in negative socioemotional reactions ( P = .001) and time‐workload pressures ( P = .001). Discussion: To the best of our knowledge, this is the first study to attempt to assess the factors proposed by the functional perspective in cancer MDTs. One novel finding is the effect of sociocognitive factors on team DM quality, while another is the cognitive‐catch 22 effect: while the case discussions are significantly simpler in the second half of the meeting, there is significantly less time left to discuss the remaining cases, further adding to the cognitive taxation in teams who are now rapidly attempting to close their time‐workload gap. Implications are discussed in relation to quality and safety. Abstract : To the best of our knowledge, this is the first study to attempt to assess the factors proposed by the functional perspective in the context of cancer MDT meetings. Validated observational instruments were used to measure quality of decision making, interactions, and complexity of 822 case discussions across 3 cancer teams and 30 of their weekly meetings. One novel finding is unraveling the sociocognitive predictors of team DM quality, while another is the cognitive‐catch 22 effect